Diagnostic Accuracy of Diffusion-Weighted Magnetic Resonance Imaging Versus Positron Emission Tomography/Computed Tomography for Early Response Assessment of Liver Metastases to Y90-Radioembolization. Issue 6 (December 2015) - Barabasch, Alexandra; Kraemer, Nils A.; Ciritsis, Alexander; Hansen, Nienke L.; Lierfeld, Marco; Heinzel, Alexander; Trautwein, Christian; Neumann, Ulf; Kuhl, Christiane K.
<x xml:space="preserve">Abstract</x> Objectives Patients with hepatic metastases who are candidates for Y90-radioembolization (Y90-RE) usually have advanced tumor stages with involvement of both liver lobes. Per current guidelines, these patients have usually undergone several cycles of potentially hepatotoxic systemic chemotherapy before Y90-RE is at all considered, requiring split (lobar) treatment sessions to reduce hepatic toxicity. Assessing response to Y90-RE early, that is, already after the first lobar session, would be helpful to avoid an ineffective and potentially hepatotoxic second lobar treatment. We investigated the accuracy with which diffusion- weighted magnetic resonance imaging (DWI-MRI) and positron emission tomography/computed tomography (PET/CT) can provide this information. Methods An institutional review board–approved prospective intraindividual comparison trial on 35 patients who underwent fluorodeoxyglucose PET/CT and DWI-MRI within 6 weeks before and 6 weeks after Y90-RE to treat secondary-progressive liver metastases from solid cancers (20 colorectal, 13 breast, 2 other) was performed. An increase of minimal apparent diffusion coefficient (ADCmin) or decrease of maximum standard uptake value (SUVmax) by at least 30% was regarded as positive response. Long-term clinical and imaging follow-up was used to distinguish true- from false-response classifications. Results On the basis of long-term follow-up, 23 (66%) of 35 patients responded to the Y90 treatment. No significant changes of metastases size or contrast enhancement were observable on pretreatment versus posttreatment CT or magnetic resonance images.However, overall SUVmax decreased from 8.0 ± 3.9 to 5.5 ± 2.2 (P < 0.0001), and ADCmin increased from 0.53 ± 0.13 × 10−3 mm2/s to 0.77 ± 0.26 × 10−3 mm2/s (P < 0.0001). Pretherapeutic versus posttherapeutic changes of ADCmin and SUVmax correlated moderately (r = −0.53). In 4 of the 35 patients (11%), metastases were fluorodeoxyglucose-negative such that no response assessment was possible by PET. In 25 (71%) of the 35 patients, response classification by PET and DWI-MRI was concordant; in 6 (17%) of the 35, it was discordant. In 5 of the 6 patients with discordant classifications, follow-up confirmed diagnoses made by DWI. The positive predictive value to predict response was 22 (96%) of 23 for MRI and 15 (88%) of 17 for PET. The negative predictive value to predict absence was 11 (92%) of 12 for MRI and 10 (56%) of 18 for PET. Sensitivity for detecting response was significantly higher for MRI (96%; 22/23) than for PET (65%; 15/23) (P < 0.02). Conclusions Diffusion-weighted magnetic resonance imaging appears superior to PET/CT for early response assessment in patients with hepatic metastases of common solid tumors. It may be used in between lobar treatment sessions to guide further management of patients who undergo Y90-RE for hepatic metastases.